Building Linking Capital Through Religious Activity to Improve Educational Character - Syaharuddin Syaharuddin; Mutiani Mutiani; Muhammad Rezky Noor Handy; Ersis Warmansyah Abbas; Rusmaniah Rusmaniah (AL-ISHLAH: Jurnal Pendidikan, 2022)
This study aims to describe how to build network social capital through religious activities to improve character education. A qualitative approach is used to describe the religious activities carried out by the Banjar community. Interviews involving 15 sources a structured and conducted. Observations and documentation studies were carried out in Basirih and Mantuil sub-districts. Miles and Huberman's analytical technique model reduces research data from interviews. The study results describe that in the Banjar community, a religious activity that has been carried out from generation to generation until now is known as Bahandil Yasinan (reading of Yasin among residents). Bahandil Yasinan is carried out by both men and women. Bahandil Yasinan in building linking capital network relationships is represented through administrators, members, and participants who discuss social issues at each meeting. This problem is not only limited to material activities but also outside the context of these recitation activities. Linking capital serves as a system of communication channels to protect and promote interpersonal relationships. Thus, the established linking capital is able to increase emotional closeness between the Banjar community.